Non-Linear Inductors Characterization in Real Operating Conditions for Power Density Optimization in SMPS - Daniele Scirè; Gianpaolo Vitale; Marco Ventimiglia; Giuseppe Lullo (Energies, 2021)
The exploitation of power inductors outside their linear region in switching converters can be achieved by raising the current until a decrease in the inductance can be noticed. This allows using a smaller magnetic core, increasing the power density of the converter. On the other hand, a detailed description of the magnetization curve including the temperature is required. Since this information is often not included in the inductor’s datasheets, this paper shows how to identify the behavior of an inductor when it is operated up to saturation and its temperature rises. In order to characterize the inductor in real operating conditions, a dedicated measurement rig was developed. It consists of a switching converter that encompasses the inductor under test and is controlled by a virtual instrument developed in LabVIEW. The characterization system was tested by retrieving the inductance and the magnetization curves vs. current for two commercial inductors at core temperatures up to 105 °C. The magnetic core was then characterized by the saturation current vs. inductance, obtaining an expression for the whole family of inductors sharing the same core. Finally, we experimentally analyzed the thermal transient of the inductors in operating conditions, confirming the fundamental role of the temperature in changing the current profiles and the core saturation condition.